Primary Hydatid Cyst of the Kidney and Ureter with Hydatiduria in a Laboratory Worker: A Case Report - Venkatesh Seetharam; Vinay Khanna; Padmapriya Jaiprakash; Kranthi Kosaraju; Joseph Thomas; Chiranjay Mukhopadhayay (Case Reports in Nephrology)
Hydatid disease is frequent in endemic regions and sheep farming areas. Most common localization of hydatid cyst occurs in liver followed by lungs. Renal hydatid cyst constitutes about 2–4% of all locations. We report a case of left renal hydatid from a laboratory technician admitted in a tertiary care hospital. There were few cases of renal hydatid disease reported in India among general population but to the best of our knowledge never reported from laboratory worker. The possibility of laboratory-acquired infection cannot be ruled out in this case due to lack of precautionary measures and containment facilities in resource-constrained setting.